2017
DOI: 10.1007/s13197-017-2608-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant properties of Za’atar (Thymbra spicata) essential oils as natural antioxidant for stability of palm olein during deep-fat frying process

Abstract: The yield of Za'atar () essential oils were found to be 2.5-3.4% at extraction process temperatures of 100-175 °C. The essential oils contained 79.5-86.2% carvacrol. Effects of BHT and Za'atar essential oil on stability of palm olein during deep-fat frying of potato slices were studied at 180 °C. Changes in peroxide, para-anisidine, iodine values, free fatty acid and color were determined. Za'atar essential oil and BHT reduced free fatty acid content of olein from 0.27 to 0.21% (oleic acid) after 50 frying cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
5
6
0
Order By: Relevance
“…The values for AV, PV, q-AnV and TOTOX of control group significantly increased À1 , 5.43 and 195.63, respectively. Furthermore, the results also indicated that the addition of MLEO at 1600 mg kg À1 in sunflower oil was able to inhibit the development of free fatty acids, primary and secondary oxidation products, which was in agreement with the several previous studies (Maskan, & Horuz, 2017;Chandran et al, 2017).…”
Section: Effects Of Mleo On Av Pv Q-anv and Totoxsupporting
confidence: 91%
See 1 more Smart Citation
“…The values for AV, PV, q-AnV and TOTOX of control group significantly increased À1 , 5.43 and 195.63, respectively. Furthermore, the results also indicated that the addition of MLEO at 1600 mg kg À1 in sunflower oil was able to inhibit the development of free fatty acids, primary and secondary oxidation products, which was in agreement with the several previous studies (Maskan, & Horuz, 2017;Chandran et al, 2017).…”
Section: Effects Of Mleo On Av Pv Q-anv and Totoxsupporting
confidence: 91%
“…For instance, at 1600 ppm, the addition of lemonverbena essential oil to sunflower oil could enhance the oxidative stability of sunflower oil and retard its lipid oxidation (Farahmandfar et al, 2018). Maskan & Horuz (2017) demonstrated that Za'atar (Thymbra spicata) was able to restrain the oxidative degradation of palm olein during frying process by means of its essential oil. Quite interestingly, essential oils not only increase the antioxidant activity of vegetable oils, but also improve the sensory properties and consumers' acceptability of them by its flavour characteristics (Chandran et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Quite interestingly, the synergistic effect of ADEO and TBHQ in inhibiting the oxidation of sunflower oil was perfectly demonstrated. Recently, the essential oil from Teucrium polium was demonstrated to suppress the changes for AV and PV during the storage of canola oil, and the essential oil of Thymbra spicata was found to suppress the alteration of PV and AnV in the deep-fat frying procedure of palm olein [29,30]. The results were in conformity with these reports.…”
Section: The Effect Of Adeo On Oxidative State Of Sunflower Oilsupporting
confidence: 80%
“…The essential oils of T. spicata were used as natural antioxidants to stabilize palm oil during deep‐fat frying and in Turkish dry‐fermented sausage . The essential oils of S. thymbra are active antioxidants in the carotene–linoleic acid system, prevent the Cu 2+ ‐mediated oxidation of low‐density lipoprotein (LDL), and show activity in 2,2‐azino‐bis (3‐ethylbenzothiazloine‐6‐sulphonic acid) radical cation (ABTS) and 1,1‐diphenyl‐2‐picrylhydrazyl radical (DPPH) assays …”
Section: Introductionmentioning
confidence: 99%